Estimativas de Strichartz e a equação não linear de Schrödinger em espaços euclidianos. - Santos, Alex Santana dos (2009)
In this work we will study local and global well-posedness to Schrödinger nonlinear equation, with initial data L2(RN), that is iut(t,x) + Δu(t,x) = γ│u(t,x)│α u(t, x) u(x,0) = φ(x) L2(RN), x RN, t R. where u is a complex value function and 0 < α <4/ N .